Aberrant Protein Turn-Over Associated With Myofibrillar Disorganization in FHL1 Knockout Mice - Ding, Jingjing; Cong, Yan Fei; Liu, Bo; Miao, Jianing; Wang, Lili (Frontiers in Genetics, 2018)
Mutations in the FHL1 gene, and FHL1 protein deletion, are associated with rare hereditary myopathies and cardiomyopathies. FHL1-null mice develop age-dependent myopathy and increased autophagic activity. However, the molecular pathway involved in contractile function and increased autophagic activity in the FHL1-null mouse has not yet been fully elucidated. In this study, FHL1 protein was knocked out in mice using Transcription Activator-like Effector Nucleases (TALENs) and the IRS1-FOXO1/mTOR signaling pathway was investigated in skeletal muscles and heart. TALEN constructs caused targeted mutations in 30% of newborn mice; these mutations caused a deletion of 1 to 13 base pairs which blocked synthesis of the full-length FHL1 protein. Furthermore, 2.5-month old FHL1-null male mice were not prone to global muscular fatigue when compared with WT littermates, but histological analysis and ultrastructural analysis by transmission electron microscopy confirmed the presence of myofibrillar disorganization and the accumulation of autophagosome or autolysosome-like structures in FHL1-null mice. Moreover, autophagy and mitophagy were both activated in FHL1 KO mice and the degradation of autophagic lysosomes was impeded.Enhanced autophagic activity in FHL1 KO mice was induced by FOXO1 up-regulation and protein synthesis was increased via mTOR. The cytoskeletal proteins, MYBPC2 and LDB3, were involved in the formation of pathological changes in FHL1 KO mice.Markers of early differentiation (MEF2C and MYOD1) and terminal differentiation (total MYH) were both up-regulated in tibialis anterior (TA) muscles in FHL1 KO mice. The number of type I and type II fibers increased in FHL1-null TA muscles, but the number of typeⅡb, and typeⅡd fibers were both reduced in FHL1-null TA muscles. The results obtained from the heart were consistent with those from the skeletal muscle and indicated autophagic activation by FOXO1 and an increase in protein synthesis via mTOR also occurred in the heart tissue of FHL1 knockout mice. In conclusion, aberrant protein turn-over associated with myofibrillar disorganization in FHL1 knockout mice. the up-regulation of FOXO1 was associated with enhanced autophagic activity and pathological changes in the muscle fibers of FHL1 KO mice. These results indicated that autophagy activated by FOXO1 is a promising therapeutic target for hereditary myopathies and cardiomyopathies induced by FHL1.